Analysis of the perception of young university students regarding the tuning of television programs with religious content of social conflict during the context of the COVID-19 pandemic, Peru 2020 - Serrato Sánchez, Segundo (2021)
During the quarantine established by the COVID-19 pandemic, peruvian families extended their hours of attention to television, and demonstrated a preference for programs that present topics related to religiosity and domestic violence. Based on a systematization of audience ratings in Lima and six regions, the perception of young university students regarding the reasons for this preference was investigated. A survey was applied to 100 young university students about the rating registered between March 15 and June 30, 2020, of the soap opera “La rosa de Guadalupe” (in Mexican and Peruvian versions) and the “Nunca más”. It was concluded that both programs are preferred because they reflect situations that are familiar and resemble reality. It is also evidenced that television is the most influential medium for the dissemination of social patterns, due to its hegemonic presence in homes and due to its great expressive force to transmit messages from daily life.